OPTIMALISASI POTENSI WADUK BUGEL INDAH DAN MAKAM HABIB DESA LEUWIGEDE KECATAMAN WIDASARI KABUPATEN INDRAMAYU JAWA BARAT MENUJU DESA WISATA - Zaenal Faizin; Juniperus Chinensis Linn; Den Rama Purba; Muhammad Arif Syarif (Swadaya: Indonesian Journal of Community Empowerment, 2021)
Villages have a lot of potential that is still untapped or not properly processed, especially in the tourism sector. Therefore, the theme of the UMC KKN is Exploring the Potential of Tourism Villages Towards West Java Champion During the Covid-19 Pandemic, basically every village has potential that sometimes the surrounding community itself has not seen this potential, such as in Leuwigede village, there are already natural resources and resources. adequate human. Whereas the tourism sector is one source of income and is able to make a very good contribution to village independence. Recently, tourists have switched from conventional tourism to tourism that has a sense of caring for the environment, nature, and culture. Tourism that gives respect to the environment, nature, and culture cannot be separated from the support of the environment in the village, which is driven to support the potential of rural tourism. Each village has a uniqueness that can be a special attraction for the village. The charm of each village can be seen immediately or requires effort to dig up again. Tourist attractions can be in the form of natural potentials such as mountains, lakes, rivers, beaches, seas, or cultural potentials such as customs, museums, forts, historical heritage sites, and others, as well as man-made potential. A tourist area must have a different attraction from one another. Every village can become a tourist place if the community, organization and government can cultivate the potential of the village. Keywords: Tourism Village, Natural and Cultural Potential